Manajemen Pengelolaan Badan Usaha Milik Desa (BUMDes) Unggul Bahtera di Desa Babakan Kecamatan Karanglewas Kabupaten Banyumas - Novita Febrian; Yeni Fitria; Nur Afidah; Maratun Nafi’ah A.Z; Sinta Nur A.Z (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Village-Owned Enterprises are pivotal in driving village development through sustainable management of local resources. This study analyzes the management of Unggul Bahtera BUMDes in Babakan Village, Banyumas Regency, focusing on planning, organizing, implementation, and evaluation, as well as the factors that support and hinder its progress. Employing a descriptive qualitative approach, data were gathered through interviews, observations, and documentation. The findings reveal that while BUMDes Unggul Bahtera has demonstrated effective planning and implementation, marked by participatory strategies and strong institutional coordination, it faces challenges in evaluation, particularly in enhancing supervision and reporting mechanisms. Key supporting factors include strong village government backing and active community participation, whereas limitations in human resources and business capital pose significant challenges. This research provides valuable insights into the management of BUMDes and highlights the importance of addressing evaluation gaps to ensure long-term sustainability. The findings are expected to serve as a reference for other villages in managing BUMDes more professionally and sustainably, promoting inclusive economic development. By identifying best practices and areas for improvement, this study contributes to enhancing the role of BUMDes in fostering rural economic growth and community empowerment. Ultimately, it offers practical recommendations for policymakers and practitioners seeking to optimize BUMDes performance.